2016
DOI: 10.1177/1475921716645107
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-acoustic modulation–based damage identification in a composite skin–stiffener structure

Abstract: The vibro-acoustic modulation method is applied to a composite skin-stiffener structure to investigate the possibilities to utilise this method for damage identification in terms of detection, localisation and damage quantification. The research comprises a theoretical part and an experimental part. An impact load is applied to the skin-stiffener structure, resulting in a delamination underneath the stiffener. The structure is interrogated with a low frequency pump excitation and a high frequency carrier excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…A similar result was obtained in Ref. 70 showing that increased amplitude modulation effects are measured at the damaged area, whereas there is no direct relation between the location of the damage and the frequency modulation. The authors in Ref.…”
Section: Signal Processingsupporting
confidence: 70%
“…A similar result was obtained in Ref. 70 showing that increased amplitude modulation effects are measured at the damaged area, whereas there is no direct relation between the location of the damage and the frequency modulation. The authors in Ref.…”
Section: Signal Processingsupporting
confidence: 70%
“…Recent studies assumed that AM and PM/FM are caused by different physical effects. 13 Donskoy and Ramezani 2 suggest that FM may better indicate early fatigue damage, while Hu et al 1 found that AM correlates better with the size of large, visible cracks. In our experiments, we cannot confirm that either AM or PM/FM is a reliable indicator on its own.…”
Section: Discussionmentioning
confidence: 99%
“…The standard approach for splitting a signal into instantaneous amplitude (IA) and IP is the HT, which has been used in some recent work on VAM. 1,3 The STFT is not equivalent to HT, but it is an approximation that is sufficient for VAM, where the pumping frequency is much smaller than the probing frequency, that is, the modulation happening within a single chunk during STFT is negligible.…”
Section: Separation Of Am and Pmmentioning
confidence: 99%
See 2 more Smart Citations